Adult myeloid leukaemia, geology, and domestic exposure to radon and gamma radiation: a case control study in central Italy. Issue 2 (February 1998) - Forastiere, F; Sperati, A; Cherubini, G; Miceli, M; Biggeri, A; Axelson, O
Abstract : OBJECTIVES: To investigate whether indoor randon or gamma radiation might play a part in myeloid leukaemia as suggested by studies based on crude geographical or geological data for exposure assessment. METHODS: For six months randon and gamma radiation was measured with solid state nuclear track detectors and thermoluminescent dosimeters in dwellings of 44 adult male cases of acute myeloid leukaemia and 211 controls (all subjects deceased). Conditional logistic regression ORs (ORs) and 95% confidence intervals (95% CIs) were estimated for quartiles of radon and gamma radiation and for municipality and dwelling characteristics. RESULTS: The risk of leukaemia was associated with an increasing urbanisation index (p value for trend = 0.008). An increased OR was found among those living in more modern houses (OR 3.0, 95% CI 1.4 to 6.6). Confirming the findings of a previous study in the same area, geological features bore a positive association with myeloid leukemia, even by adjusting for level of urbanisation. Contrary to expectations from the previous study, however, no association appeared between myeloid leukaemia and radon and gamma radiation; for the highest quartiles of exposure, ORs were 0.56 (95% CI 0.2 to 1.4) and 0.52 (95% CI 0.2 to 1.4), respectively. Considering only subjects who had lived > or = 20 years in the monitored home and adjusting for urbanisation, there was still no effect of exposure to radiation. CONCLUSIONS: In view of the limited numbers, the results do not in general refute a possible risk of myeloid leukaemia from exposure to indoor radon or gamma radiation, but decrease the credibility of such a relation in the area studied and also of other studies suggesting an effect without monitoring indoor radiation. Some other fairly strong determinants have appeared–that is, level of urbanisation and living in modern houses–that might need further consideration.